Penyuluhan UMKM Berbasis Syariah Pada Siswa Sekolah Entrepreneur Global Cahaya Nubuwah Insani Purwakarta - AA Hubur; Medina Nilasari; Robert Kristaung (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The Sharia-based MSME market is attracting the attention of most of the Muslim community. However, this attraction will only come to fruition if the idea and execution adhere to strict Sharia principles. Although many MSMEs call themselves Sharia-based, the reality is often far from this ideal. This study aims to provide an in-depth understanding of the concepts and applications of Shariah-based MSMEs to the students of Global Cahaya Nubuwah Insani Purwakarta School of Entrepreneurship, especially regarding financial resources, processes production and marketing strategy. The dedication method used was the usual one through presentations made by two curators with expertise in aspects of Sharia contracts and operational aspects of MSMEs. The results showed that the students understood the basic concepts of Sharia-based MSME, including finance, production, and marketing. However, one of the identified obstacles is limited practical experience in managing these MSMEs. By providing these tips, we hope that Entrepreneurship School students can absorb Sharia-based MSME theory and be able to apply it in a real-world setting. The implementation is mainly focused on Sharia-compliant funding sources, Sharia-guided manufacturing processes, and Sharia-based marketing strategies. With better understanding and implementation, it is hoped that Sharia-based MSMEs can thrive by adhering to a solid foundation of highly respected Sharia principles.